PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN - Faisal, Yusuf; Indriyani, Indriyani; Mayang, Titin; Muhamad4, Adam (Politeknik Negeri Ambon, 2023)
The purpose of the study is to find out empirically the effect of competence of human resources and accounting information systems on the quality of financial reports. This research is stand as empirical research by used saturation sampling as sampling technique. The survey method was used in data collection and hypothesis testing through t-statistical test with a significance level of 0.05. The results of the study prove that the understanding of competence of human resources has no significant positive effect on the quality of financial statements, but the accounting information systems has a significant positive effect on the quality of financial reports Mitra Madani Sejahtera Cooperative.